Influences of environmental factors on the microbial community characteristics of bioaerosols in a cold region - Nami Lai; Shuozhen Tian; Silu Wang; Xiaoyan Wang; Ruihan Chen; Yuwei Liu; Huize Yang; Mengying Wang; Xiaoyu Cai; Wanying Yao; Shuling Li; Yue Xiao; et al. (Journal of Environmental Sciences, 2026)

Herbacetin alleviates acute doxorubicin cardiotoxicity via regulating the ERK1/2-FOXO3a signaling pathway - Sijia Bian; Xinran Li; Peiyan Zhu; Zhiting Jiang; Chen Yan; Shuling Wei; Liqi Luo; Yuhua Zhu; Lan Luo (Human Cell, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Molecular evidence for microbial methane oxidation associated with complete ammonia oxidizers in paddy soils - Zongjing Kang; Shuling Wang; Lu Lu; Xia Zhu-Barker; Junji Yuan; Yongxin Lin; Zhongjun Jia; Alan L. Wright; Andreas Kappler; Sara Kleindienst; Xianjun Jiang (Soil Biology and Biochemistry, 2025)

Discovery, engineering, and applications of the ketoreductases from Metabacillus lacus in the synthesis of chiral (Hetero)aryl alcohols - Shuling Zhang; Yuqing Zhang; Weixi Kong; Wanting Guo; Quan Yuan; Yanjun Jiang; Yunting Liu (Chemical Engineering Journal, 2025)

Responses of complete and incomplete ammonia oxidizers to farmland reversion to forest in Ferralsols - Pengfei Zhang; Yongpeng Zhao; Lihua Ma; Shuling Wang; Min Yang; Alan L. Wright; Xianjun Jiang (Applied Soil Ecology, 2025)

Measurement and modelling of soil water dynamics under ridge tillage in paddy field - Lihua Ma; Shuling Wang; Chengsheng Ni; Wene Wang; Shaozhong Kang; Zhaolei Li; Alan L. Wright; Xianjun Jiang (Soil and Tillage Research, 2024)

Stability of nitrogen-cycling microbial communities and impact on microbial nitrogen function under different land use practices - Yongpeng Zhao; Zhihui Wang; Kai Cai; Shuling Wang; Alan L. Wright; Xianjun Jiang (Applied Soil Ecology, 2024)

Inhibitiory mechanism of phloretin on xanthine oxidase and its synergistic effect with allopurinol and febuxostat - Jiaqi Wen; Shuling Chen; Le Deng; Xinru Chen; Xiaoyu Jiang; Xing Hu; Deming Gong; Guowen Zhang (Food Bioscience, 2024)

Influence of Fe substitution on structural stability and hydrogen storage/compression performance: A theoretical and experimental study on TiCr1.5-Mn0.5Fe alloys - Wenbin Jiang; Shuling Chen; Hanhao Shen; Zhijie Cao; Changchun He; Xiaobao Yang; Liuzhang Ouyang (Chemical Engineering Journal, 2024)

Insights into the catalytic mechanism of V-Mo@CN for the oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran - Shibo Yang; Tong Sun; Xiaokai Li; Wenbo Liao; Jianfei Bian; Xing Tang; Shuling Yang; Lu Lin; Wei Jiang; Lincai Peng; Yong Sun (Chemical Engineering Journal, 2024)

Insights into boosting catalytic hydrogen evolution over Co doping Ru nanoparticles - Hao Wen; Ruofan Shen; Yanyan Liu; Xiaoyan Huang; Shuling Liu; Zhikun Peng; Xianli Wu; Xianji Guo; Erjun Liang; Huiyu Yuan; Baojun Li; Jianchun Jiang (Fuel, 2023)

Bacterial diversity of middle ear cholesteatoma by 16S rRNA gene sequencing in China - Qiulin Liang; Ruiqing Long; Shuling Li; Chaowu Jiang; Jingyu Gao; Sheng Cheng; Zhuohui Liu; Biao Ruan (Functional & Integrative Genomics, 2023)
In this study, the bacterial diversity of acquired middle ear cholesteatoma (MEC) was evaluated to reveal its pathogenesis and provides a guide for the use of antibiotics. Twenty-nine cases of acquired MEC and eight cases of healthy middle ears undergoing cochlear implantation (CI) were evaluated. Full-length 16S rRNA gene sequencing was performed to profile the bacterial communities in lesions and healthy tissues of the middle ear. ACE ( P = 0.043) and Chao1 ( P = 0.039) indices showed significant differences in alpha diversity ( P < 0.05). Analysis of PERMANOVA/Anosim using the Bray–Curtis distance matrix results suggested that the between-group differences were greater than the within-group differences ( R = 0.238, P < 0.05, R 2 = 0.066, P < 0.05). Bacterial community analysis revealed that Alphaproteobacteria at the class level and Caulobacterales and Sphingomonadales at the order level were significantly different ( P < 0.05). In the LefSe (Linear discriminant analysis effect size) analysis, Porphyromonas bennonis was elevated, and Bryum argenteum and unclassified Cyanobacteriales were reduced at the species level in MEC ( P < 0.05). Fifteen metabolic pathways were found to be significantly different between the two groups by analysing the abundance of metabolic pathways in level 2 of the Kyoto Encyclopaedia of Genes and Genomes (KEGG). Seven and eight metabolic pathways were significantly elevated in the MEC and control groups, respectively ( P < 0.05). The role of bacteria in the pathogenesis of acquired MEC was further refined through analysis of metabolic pathways. These findings indicate that the acquired MEC and healthy middle ear contain more diverse microbial communities than previously thought.

Oxygen availability, rather than ammonia, plays an important role in niche differentiation between comammox Nitrospira and canonical ammonia oxidizers in a neutral purple paddy soil - Shuling WANG; Zhihui WANG; Yongpeng ZHAO; Alan L. WRIGHT; Xianjun JIANG (Pedosphere, 2023)

Environmental pseudotargeted metabolomics: A high throughput and wide coverage method for metabolic profiling of 1000-year paddy soil chronosequences - Kai Cai; Yongpeng Zhao; Zongjing Kang; Shuling Wang; Alan L. Wright; Xianjun Jiang (Science of The Total Environment, 2023)

Effect of urea feeding on transforming and migrating soil fluorine in a tea garden of hilly region - Hua Long; Yamei Jiang; Chaoqun Li; Shuling Liao; Shuyu Shi; Chunping Huang; Shilin Zhao; Xiaoting Li; Yang Liao (Environmental Geochemistry and Health, 2021)

Characterization of Water Quality in Xiao Xingkai Lake: Implications for Trophic Status and Management - Shuling Yu; Xiaoyu Li; Bolong Wen; Guoshuang Chen; Anne Hartleyc; Ming Jiang; Xiujun Li (Chinese Geographical Science, 2021)

Redox-driven shifts in soil microbial community structure in the drawdown zone after construction of the Three Gorges Dam - Shuling Wang; Sarwee J. Faeflen; Alan L. Wright; Xia Zhu-Barker; Xianjun Jiang (Soil Ecology Letters, 2019)

Pyr-miR171f-targeted PyrSCL6 and PyrSCL22 genes regulate shoot growth by responding to IAA signaling in pear - Shuling Jiang; Qiuju Chen; Qiulei Zhang; Yi Zhang; Ningning Hao; Chunqing Ou; Fei Wang; Tianzhong Li (Tree Genetics & Genomes, 2018)

Characterization and prevalence of a novel white spot syndrome viral genotype in naturally infected wild crayfish, Procambarus clarkii, in Shanghai, China - Luzhi Jiang; Jinzhou Xiao; Liyuan Liu; Yingjie Pan; Shuling Yan; Yongjie Wang (VirusDisease, 2017)

Genome-wide methylation changes are associated with muscle fiber density and drip loss in male three-yellow chickens - Yonghong Zhang; Jiang Guo; Yan Gao; Shuling Niu; Chun Yang; Chunyan Bai; Xianzhong Yu; Zhihui Zhao (Molecular Biology Reports, 2014)

Expression of glr gene encoding glutamate racemase in Bacillus licheniformis WX-02 and its regulatory effects on synthesis of poly-γ-glutamic acid - Feng Jiang; Gaofu Qi; Zhixia Ji; Shuling Zhang; Jun Liu; Xin Ma; Shouwen Chen (Biotechnology Letters, 2011)

Oct4 is expressed in Nestin-positive cells as a marker for pancreatic endocrine progenitor - Hong Wang; Shuling Wang; Jiang Hu; Yaxian Kong; Shen Chen; Lingsong Li; Liying Li (Histochemistry and Cell Biology, 2009)